2020
DOI: 10.3390/genes11040423
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Auxotrophy Affects Siderophore Biosynthesis and Attenuates Virulence of Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an opportunistic human pathogen mainly infecting immunocompromised patients.The aim of this study was to characterize the role of arginine biosynthesis in virulence of A. fumigatus via genetic inactivation of two key arginine biosynthetic enzymes, the bifunctional acetylglutamate synthase/ornithine acetyltransferase (argJ/AFUA_5G08120) and the ornithine carbamoyltransferase (argB/AFUA_4G07190). Arginine biosynthesis is intimately linked to the biosynthesis of ornithine, a precursor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…We also detected a series of metabolic pathways that showed apparent species specificity, most of which have been reported to be associated with virulence and adoption of pathogenic organisms. For example, the role of arginine biosynthesis in virulence has been reported to be crucial for full virulence of Aspergillus fumigatus in insects ( Dietl et al, 2020 ), and we have showed that the pathway of arginine biosynthesis in M. curtisii and M. mulieris was different, perhaps suggesting a different utilizing efficiency. Furthermore, the capabilities of MoCo biosynthesis and nitrate reduction were only found in M. curtisii strains, both of which have been implicated in pathogenesis of a number of bacterial infections ( Williams et al, 2011 ; Andreae et al, 2014 ; Almeida et al, 2017 ); more his genes were found in M. curtisii strains, perhaps enabling them capacity of biosynthesis of histidine and a crucial role in metal homeostasis and virulence ( Dietl et al, 2016 ); and the extra NAD + de novo biosynthesis pathway in M. curtisii could also enhance their virulence during host infection ( Dom and Haesebrouck, 1992 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 75%
“…We also detected a series of metabolic pathways that showed apparent species specificity, most of which have been reported to be associated with virulence and adoption of pathogenic organisms. For example, the role of arginine biosynthesis in virulence has been reported to be crucial for full virulence of Aspergillus fumigatus in insects ( Dietl et al, 2020 ), and we have showed that the pathway of arginine biosynthesis in M. curtisii and M. mulieris was different, perhaps suggesting a different utilizing efficiency. Furthermore, the capabilities of MoCo biosynthesis and nitrate reduction were only found in M. curtisii strains, both of which have been implicated in pathogenesis of a number of bacterial infections ( Williams et al, 2011 ; Andreae et al, 2014 ; Almeida et al, 2017 ); more his genes were found in M. curtisii strains, perhaps enabling them capacity of biosynthesis of histidine and a crucial role in metal homeostasis and virulence ( Dietl et al, 2016 ); and the extra NAD + de novo biosynthesis pathway in M. curtisii could also enhance their virulence during host infection ( Dom and Haesebrouck, 1992 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 75%
“…3B ). It is reported that the bifunctional argJ has been found in Aspergillus fumigatus , Saccharomyces cerevisiae , and Thermophilic microorganisms ( 35 37 ). The present study showed that ahrC deletion significantly upregulated argB , argC , argD , argF , argJ , argG , and argH , indicating that ahrC is closely associated with the S. mutans arginine biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The glutamate family includes glutamate and other derived glutamine, proline, and arginine from glutamate; and lysine sometimes is included in this family. The biosynthesis of glutamate and glutamine is a key step in the nitrogen assimilation ( Kwan et al, 2015 ; Dietl et al, 2020 ). Generally, the enzymes glutamine oxoglutarate aminotransferase and glutamate dehydrogenase catalyze the nitrogen assimilation reactions.…”
Section: Discussionmentioning
confidence: 99%